Construction Management Planning for the Development of Hotel Prisma Indah V Floor Kertajati Majalengka - Apidi, Muhammad; H, Andhika Tresna (Devotion : Journal of Research and Community Service, 2025)
Construction management is the process of planning, organizing, and supervising construction projects to ensure they are completed on time, within the specified budget, and at the expected quality. This research aims to enhance and develop knowledge in construction management. It provides an overview and input on controlling project time and costs. It also seeks to determine the work volume, construction costs, the bar chart, and the S-curve analysis. Construction management planning for the construction of the Prisma Indah V floor hotel in Kertajati Majalengka includes volume calculations, bar charts, RAB, Cost Recap, and AHSP in the Majalengka area, using data collection methods (direct field observation and searching for theories in the library), data types (primary data and secondary data), and data sources. This study identifies the construction management stages of the project: preparatory work, foundation, ground floor, 1st floor, 2nd floor, 3rd floor, 4th floor, and roof floor. By calculating the work weight through bar chart analysis, S-curve, and CPM for the construction of the Prisma Indah V-floor hotel building in Kertajati Majalengka, we obtained the suggested volume in our report and estimated the completion of the work within 42 weeks or 294 days, with costs of approximately IDR 12,119,000,000 (Twelve Billion One Hundred Nineteen Million Rupiah).